FORMATION OF AN INTERNAL ESG SYSTEM OF A BUSINESS ENTITY - ANISIMOVA, Olga; SIDORENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyses the basic principles and approaches to building an internal ESG system at an enterprise. The aim of the study is to identify opportunities for creating an effective internal ESG system of an enterprise to integrate the principles of sustainable development into its business activities.It is established that it is necessary to introduce a holistic approach to the integration of ESG parameters into the enterprise management system. This involves creating an effective system of data collection and analysis, unification of reporting forms, transparency in social and managerial activities, and formulation of a long-term sustainable development strategy. An important advantage of ESG integration is the ability of businesses to reduce operating costs, increase customer and partner trust, attract sustainability-oriented investors, and maintain sustainability in a changing market environment.The process of ESG integration includes the transition to environmentally friendly technologies, the implementation of social programmes focused on employees and communities, and adherence to high standards of corporate governance. Of particular importance is the involvement of employees and the creation of a culture of responsibility that promotes support for ESG initiatives at all levels of the organisation.To assess the effectiveness of ESG integration, it is necessary to implement modern monitoring systems, automated analysis tools and regular reporting in accordance with international standards. An important element is the company's openness to external audits and independent assessment of ESG indicators.At the same time, companies face challenges, such as the need for significant investments, difficulty in determining social and environmental results, and resistance to change among employees and partners. At the same time, the benefits of ESG, such as cost optimisation, increased brand trust, access to green financing and reduced regulatory risks, make this approach strategically viable.
Keywords: ESG principles; internal ESG system; ESG ratings; ESG indexes